2018
DOI: 10.1016/j.jtumed.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a reminder card system versus a mobile application to improve medication adherence among asthma patients in a tertiary care hospital

Abstract: Objectives Asthma is a major public health problem affecting a large number of individuals worldwide. The effectiveness of medications depends on adherence to the instructions of the prescriber. This study aimed to assess and compare the effectiveness of a reminder card system versus a mobile application to improve the medication adherence of asthma patients in a tertiary care hospital. Methods This prospective interventional study was conducted at a tertiary care hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…There are 3 researches that discuss text messaging or short message services (SMS) that have been applied to various mobile phones regarding health-based intervention (mHealth). One of many strategies to increase compliance is with short message service (SMS) because this media is inexpensive and can reach a large number of people as mobile phones are common in most countries (Bediang et al, 2018) , (Mohan et al, 2018) (Elangovan & Arulchelvan, 2013). Patients receive SMS reminders every day for 6 months.…”
Section: Discussion Theme 1: Mobile Health Applicationmentioning
confidence: 99%
“…There are 3 researches that discuss text messaging or short message services (SMS) that have been applied to various mobile phones regarding health-based intervention (mHealth). One of many strategies to increase compliance is with short message service (SMS) because this media is inexpensive and can reach a large number of people as mobile phones are common in most countries (Bediang et al, 2018) , (Mohan et al, 2018) (Elangovan & Arulchelvan, 2013). Patients receive SMS reminders every day for 6 months.…”
Section: Discussion Theme 1: Mobile Health Applicationmentioning
confidence: 99%
“…The increasing of adherence in taking medicine supported the successful of therapy. A reminder card of medication was able to be used as an alternative intervention in the Ministry of Pharmacy so that the purpose of therapy for patients was able to be accomplished [26], [27], [28].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment adherence is also linked to patients’ emotional well-being, the mental strength with which they face the situation, and ultimately, their level of positive mental health [ 23 , 24 ]. It has been observed that interventions are needed to improve lack of treatment adherence [ 25 ]. No studies have been found in medical literature on the subject of pharmacological adherence and patients with femur fractures.…”
Section: Introductionmentioning
confidence: 99%